Anesthesia and Intensive Care Management in a Pregnant Woman with PRES: A Case Report - Ismail Demirel; Ayse Belin Ozer; Mustafa K. Bayar; Salih Burcin Kavak (Case Reports in Anesthesiology)
Posterior reversible encephalopathy syndrome (PRES) is a temporary condition that is diagnosed clinically, neurologically, and radiologically. Its symptoms vary, and nonspecific headaches, confusion, impairment of consciousness, nausea, vomiting, and visual impairment may occur. Acute hypertension often accompanies these symptoms. Patients can also suffer from convulsions, cortical visual impairment, and coma. Diagnosis can be difficult due to focal neurologic signs. Nevertheless, knowing the clinical risk factors can lead to the right diagnosis. It has been reported that this condition may also occur during organ transplantation, immunosuppressive treatment, and autoimmune diseases and chemotherapy, and also patients with eclampsia. In this paper, a 21-year-old, 31-week pregnant woman, who had been diagnosed with PRES and thanks to early diagnosis and treatment had fully recovered and discharged from the intensive care unit, is presented, and the relevant literature is discussed.